2021
DOI: 10.1186/s13104-021-05817-z
|View full text |Cite
|
Sign up to set email alerts
|

The importance of adherence to international standards for depositing open data in public repositories

Abstract: There has been an important global interest in Open Science, which include open data and methods, in addition to open access publications. It has been proposed that public availability of raw data increases the value and the possibility of confirmation of scientific findings, in addition to the potential of reducing research waste. Availability of raw data in open repositories facilitates the adequate development of meta-analysis and the cumulative evaluation of evidence for specific topics. In this commentary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…Open databases and basic principles of data sharing will be paramount to develop and implement AI models, allowing to reproduce results, compare the accuracy of different methods and approaches and confirming scientific findings [153] . The main barrier to modelling lies between laboratory conditions and free-living clinical and practical environments, but still the incorporation of contextual factors will ease the transference of these models to real life scenarios.…”
Section: Discussionmentioning
confidence: 97%
“…Open databases and basic principles of data sharing will be paramount to develop and implement AI models, allowing to reproduce results, compare the accuracy of different methods and approaches and confirming scientific findings [153] . The main barrier to modelling lies between laboratory conditions and free-living clinical and practical environments, but still the incorporation of contextual factors will ease the transference of these models to real life scenarios.…”
Section: Discussionmentioning
confidence: 97%
“…Open data was essential to face this pandemic, contributing to better transparency, reproducibility of results and evidence-based decision-making [2,3]. In this sense, one of the most popular tools is the Observatory tool named "Observatorio CMP" available at: https://www.cmp.org.pe/ observatorio-cmp/ that allows viewing the information of all registered medical doctors in Peru, physicians with COVID-19 (by self-report), statistics of services, physicians already vaccinated, mortality of physicians by COVID-19 in Latin America, and data about insured physicians.…”
Section: Brazilian Health Informatics Association (Sbis)mentioning
confidence: 99%
“…Thus, although some researchers have hesitations about sharing research data and protocols, the use of OD is increasing as studies have demonstrated that OD create an inclusive environment for junior researchers, increases research recognition and credibility, inspires new research ideas, and has the potential to reduce costs of future research [ 1 4 , 16 – 18 ]. Furthermore, open access (OA) to raw and processed data as well as source code and sufficient documentation of research protocols promotes FAIR principles and maximizes reproducibility [ 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%